How CSR Strategies Empower Coastal Communities to Support Indonesia's Goal of Ending Poverty A Case Study in Juntinyuat, Indramayu - Fabian Panji Ayodya; Vany Ardianto; Yedo Kurniawan (Prospect Publishing, 2025)
Poverty in coastal communities is a complex structural issue influenced by low levels of education, skills, access to capital and technology, as well as high dependency on marine capture fisheries. This study aims to develop Corporate Social Responsibility (CSR) strategies that contribute to poverty alleviation while supporting Indonesia’s national goals for sustainable development. The case study was conducted in Juntinyuat Village, Indramayu, by utilizing the potential of fisheries and local resources. The methods applied include mapping community potentials and needs, capacity building, and implementing empowerment programs. The findings reveal that the CSR program of PT Pertamina Gas OWJA through JAWARA has improved the welfare of coastal communities through: (1) empowering fishermen’s families and youth with fishery product processing training, (2) waste management based on a circular economy approach through sorting, shredding, and utilization of recyclable plastics, (3) coastal disaster mitigation by planting protective vegetation, and (4) renewable energy utilization via solar power (PLTS) to support community economic activities. The results highlight that a participatory CSR approach not only creates cost efficiency and increases household income but also strengthens socio-economic resilience and environmental sustainability in coastal communities. This CSR program has the potential to serve as a sustainable strategy model to support Indonesia’s poverty eradication agenda while preserving coastal ecosystems.